PENERAPAN SANKSI ADMINISTRATIF PELANGGARAN PROTOKOL KESEHATAN PADA MASA PANDEMI COVID-19 BERDASARKAN PERDA PROVINSI RIAU NOMOR 4 TAHUN 2020 TENTANG PERUBAHAN ATAS PERATURAN DAERAH NOMOR 21 TAHUN 2018 TENTANG PENYELENGGARAAN KESEHATAN DI KOTA PEKAN BARU - Lilik Surianto, Eddy Asnawi, Ardiansah (Madani Legal Review, 2022)
To prevent wider spread, the Indonesian government made many changes to the state constitution, which were followed by local governments. such as the example of the Riau Province Regional Regulation Number 4 of 2020 concerning Amendments to Regional Regulation Number 21 of 2018 concerning the Implementation of Health Article 44C paragraph (1) Anyone who violates the health protocol as referred to in Article 23A paragraph (2) letter a is subject to administrative sanctions in the form of: a. verbal warning; b. written warning; c. social sanctions; and/or d. administrative fine of Rp. 100,000.00 (one hundred thousand rupiah). However, in reality, the imposition of these sanctions has not run optimally. This can be seen from the fact that there are still people who lack discipline in carrying out health protocols during the COVID-19 pandemic. The formulation of the problem in this study is How, Barriers and Efforts to Implement Administrative Sanctions for Violation of Health Protocols During the Covid-19 Pandemic Based on Riau Province Regulation Number 4 of 2020 concerning Amendments to Regional Regulation Number 21 of 2018 concerning Health Administration in Pekanbaru City. The method used is sociological law research. The data sources consist of primary legal data, secondary legal data, and tertiary legal data. In this study, the data were analyzed qualitatively and in drawing conclusions the authors applied the method of deductive thinking. Based on the results of the study, it is known that the application of administrative sanctions for violations of health protocols during the Covid-19 pandemic based on the Riau Province Regional Regulation Number 4 of 2020 concerning Amendments to Regional Regulation Number 21 of 2018 concerning Health Implementation in Pekanbaru City has not gone well. This is because there are still many violations of health protocols carried out by individuals, and as a result the increase in Covid-19 cases is still increasing. Barriers to the Implementation of Administrative Sanctions for Violation of Health Protocols During the Covid-19 Pandemic Based on Regional Regulation of Riau Province Number 4 of 2020 concerning Amendments to Regional Regulation Number 21 of 2018 concerning Health Administration in Pekanbaru City are community factors, cultural factors, and limited ability of law enforcement. Efforts to Implement Administrative Sanctions for Violation of Health Protocols During the Covid-19 Pandemic Based on Regional Regulation of Riau Province Number 4 of 2020 concerning Amendments to Regional Regulation Number 21 of 2018 concerning Health Administration in Pekanbaru City is the need for the role of the community in obeying the law and maintaining health consistently at home, the need for preventive and repressive efforts in providing administrative sanctions.